2022
DOI: 10.1038/s41467-022-35216-2
|View full text |Cite
|
Sign up to set email alerts
|

Physical deep learning with biologically inspired training method: gradient-free approach for physical hardware

Abstract: Ever-growing demand for artificial intelligence has motivated research on unconventional computation based on physical devices. While such computation devices mimic brain-inspired analog information processing, the learning procedures still rely on methods optimized for digital processing such as backpropagation, which is not suitable for physical implementation. Here, we present physical deep learning by extending a biologically inspired training algorithm called direct feedback alignment. Unlike the original… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 67 publications
0
32
0
Order By: Relevance
“…For example, the training algorithm called direct feedback alignment was introduced in Ref. [300], see Figure 13. This is a universal method based on random projection with alternative nonlinear activation and requires no information about the nature of the physical system.…”
Section: Alternative Learning Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the training algorithm called direct feedback alignment was introduced in Ref. [300], see Figure 13. This is a universal method based on random projection with alternative nonlinear activation and requires no information about the nature of the physical system.…”
Section: Alternative Learning Methodsmentioning
confidence: 99%
“…Augmented DFA enables parallel, scalable, and physically accelerable training of deep physical networks based on random projection with alternative nonlinearity g(a). Reproduced with permission [300]. Copyright 2022, Springer Nature.…”
mentioning
confidence: 99%
“…The second category, deep physical neural networks (PNNs), focuses on training the hardware’s physical transformations directly to perform the desired computations. PNNs hold the promise of more scalable, energy-efficient, and faster neural network hardware by exploiting physical transformations and eliminating the conventional software-hardware separation ( 22 , 23 ).…”
mentioning
confidence: 99%
“…It has been reported that BPTT can be approximated so that RNNs can be trained in a biologically plausible manner [62,64]. Nakajima et al extended these methods and successfully trained multilayer physical RC [65]. By applying those methods to SM-RC, it is expected that SM-RC can be trained in analog and physical systems.…”
mentioning
confidence: 99%